Understanding the theme restaurant business in Singapore through comparison between Planet Hollywood, Hard Rock Cafe & Celebrities Asia - Ang, Chun Wee (2008)
This research aims to provide an understanding of the theme restaurant business in Singapore in view of the difficulties faced by these restaurants in order to survive in the industry. The critical success factors of theme restaurants are identified and the popularity of the three selected restaurants is compared. From this study, it is hoped that valuable insights are gained on the future viability of theme restaurants in Singapore.